2012
DOI: 10.1099/mic.0.054254-0
|View full text |Cite
|
Sign up to set email alerts
|

The PhzI/PhzR quorum-sensing system is required for pyrrolnitrin and phenazine production, and exhibits cross-regulation with RpoS in Pseudomonas chlororaphis PA23

Abstract: The aim of the current study was to determine how quorum sensing (QS) affects the production of secondary metabolites in Pseudomonas chlororaphis strain PA23. A phzR mutant (PA23phzR) and an N-acylhomoserine lactone (AHL)-deficient strain (PA23-6863) were generated that no longer inhibited the fungal pathogen Sclerotinia sclerotiorum in vitro. Both strains exhibited reduced pyrrolnitrin (PRN), phenazine (PHZ) and protease production. Moreover, phzA-lacZ and prnA-lacZ transcription was significantly reduced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 50 publications
7
68
0
Order By: Relevance
“…However, by extending the growth period from 24 to 48 and 72 h, we found that the production of TDA, as determined by bioactivity and pigment production, was delayed but not completely abolished. Similarly, mutations in QS genes reduced but did not totally suppress the production of biofilm-inhibiting cyclic lipopeptides in Pseudomonas putida (33) or proteases in Pseudomonas chlororaphis (34). Our results show that TDA production in P. gallaeciensis is only modulated by the PgaI-PgaR QS system, and this indicates that QS is just one of several regulatory systems involved.…”
Section: Antagonism Of P Gallaeciensis Qs Mutants In Broth Systemsmentioning
confidence: 53%
See 3 more Smart Citations
“…However, by extending the growth period from 24 to 48 and 72 h, we found that the production of TDA, as determined by bioactivity and pigment production, was delayed but not completely abolished. Similarly, mutations in QS genes reduced but did not totally suppress the production of biofilm-inhibiting cyclic lipopeptides in Pseudomonas putida (33) or proteases in Pseudomonas chlororaphis (34). Our results show that TDA production in P. gallaeciensis is only modulated by the PgaI-PgaR QS system, and this indicates that QS is just one of several regulatory systems involved.…”
Section: Antagonism Of P Gallaeciensis Qs Mutants In Broth Systemsmentioning
confidence: 53%
“…Therefore, a mutation in the QS system can lead to the complete loss of antibiotic production (31,32) or just cause a reduction in the production of the antagonistic compound (33,34). Berger et al (18) showed that TDA production in P. gallaeciensis is QS regulated.…”
Section: Antagonism Of P Gallaeciensis Qs Mutants In Broth Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies with P. chlororaphis 30-84 established that a hierarchical network of genes regulates the PhzR/PhzI QS system that controls the phenazine biosynthetic operon [16,17]. This includes regulation by the transcriptional regulator Pip, the two-component signal transduction system RpeA/ RpeB, the stationary sigma factor RpoS and the Gac/Rsm system [16][17][18][19][20]. Pip is an important positive regulator of QS in P. chlororaphis 30-84 and PCL1391 [16,18].…”
Section: Introductionmentioning
confidence: 99%